Species composition of the genus Xanthopimpla De Saussure, 1892 (Hymenoptera: Ichneumonidae, Pimplinae, Pimplini) in the Pu Mat national park, Nghe An province - Nhi, Pham Thi; Hue, Le Xuan (Academia Journal of Biology, 2014)
Five surveys on insects were conducted in the Pumat national park, Nghean province, Vietnam, during the years 2005 and 2006. Specimens of the genus Xanthopimpla De Saussure, 1892 were collected in nine transects setting up in different habitats of the park. 16 species belonging to this genus were recorded in the Pumat national park (occupied 57.14% of the total species number of this genus in Vietnam). Of which, 4 species and subspecies were new records for the Ichneumonidae fauna of Vietnam, including Xanthopimpla calva calcis Townes and Chiu, 1970; X. tricapus impressa Townes and Chiu, 1970; X. trigonophatna trigemina Krieger, 1914, and X. varimaculata Cameron, 1907. Our study also extended the distribution of the species X. alternans Krieger, 1914 northwards to the Thuathien-Hue and Nghean provinces. In Vietnam, this species previously was recorded from Gialai and Khanhhoa provinces.